Mental health in medical residents: relationship with personal, work-related, and sociodemographic variables - Karina Pereira-Lima; Sonia R. Loureiro; José A. Crippa (Brazilian Journal of Psychiatry, 2016)
Objective: To examine association of sociodemographic characteristics, personality traits, social skills, and work variables with anxiety, depression, and alcohol dependence in medical residents. Methods: A total of 270 medical residents completed the following self-report instruments: sociodemographic and work questionnaire, Patient Health Questionnaire-4 (PHQ-4), Alcohol Use Disorders Identification Test-3 (AUDIT-3), Revised NEO-Five Factor Inventory (NEO-FFI-R), and Social Skills Inventory (SSI-Del-Prette). Data were analyzed using descriptive statistics and univariate and multivariate logistic regression analyses. Results: Multivariate analysis showed an association of neuroticism (odds ratio [OR] 2.60, p < 0.001), social skills (OR 0.41, p < 0.01), and number of shifts (OR 1.91, p = 0.03) with anxiety or depression, and of male sex (OR 3.14, p = 0.01), surgical residency (OR 4.40, p = 0.001), extraversion (OR 1.80, p < 0.01), and number of shifts (OR 2.32, p = 0.04) with alcohol dependence. Conclusion: The findings support a multidetermined nature of mental health problems in medical residents, in addition to providing data that may assist in the design of preventive measures to protect the mental health of this group.